Continuing Teacher Education and its Implications for Teaching (Research, Society and Development, 2019)
The aim of this article is to investigate with teachers, aiming to find out where, how and when their continuing education happens, as well as to verify if this received formation satisfied them or not. For this purpose, we used the interview technique recorded with twenty teachers. The research was conducted in four public schools in Mato Grosso, two in Cuiabá and two in Pontes e Lacerda. This research is qualitative in nature and went through the triangulation bias, being the data categorized, coded and analyzed by the content analysis method. The survey showed that all respondents had higher education in various areas of knowledge and that all participated in the training offered in schools and they had between one and twenty five years of experience in teaching. Among other mitigating factors, the degree of teachers' (in) satisfaction was evidenced, considering the need for the trainers to know the needs and the school realities. Still, according to the interviewees, continuing education should be carried out in a local service of pedagogical practice; However, it does not mean that this way it will immediately solve the problems of a pedagogical character, but it will enable a teaching practice based on the action-reflection-action tripod.